(untitled) (Research in Agriculture Livestock and Fisheries, 2019)
The selection efficiency for certain traits in crops can be broadened using estimates of genetic parameters, which are fundamental for plant breeding. Ten maize genotypes were evaluated in randomized complete block design (RCBD) with three replications at the field of Lamahi Municipality, Dang district of Nepal to assess the magnitude of genetic variability, heritability and genetic advance for growth, yield and yield contributing traits during summer season (June to August), 2018. Analysis of variance revealed significant differences for all traits. The phenotypic coefficient of variation (PCV) was higher than genotypic coefficient of variation (GCV) recorded for all traits. The grain yield showed the highest PCV (50.78%) and GCV (51.24%) whereas the lowest PCV (4.51%) and GCV (4.50%) were recorded for test weight; test weight showed high heritability (0.99) with low genetic advance as a percent of mean (9.26). Grain yield showed positive and significant phenotypic correlation with test weight (r=0.960), kernel per row (r=0.924), kernel rows per cob (r=0.900) and cob length (r=0.840), respectively. Traits namely grain yield, number of kernels per cob and kernel rows per cob showed high GCV, PCV. Therefore these traits can be used further in crop improvement program. Res. Agric., Livest. Fish.6(2): 163-169, August 2019